A Primer for Success as an Early Career Academic Plastic Surgeon. Issue 1 (January 2022) - Lin, Lawrence O.; Barker, Jenny C.; Khansa, Ibrahim; Janis, Jeffrey E.
Abstract : Background: The early career academic plastic surgeon strives to be an expert surgeon, an innovative researcher, and an impactful educator. Navigating these challenges is difficult in a healthcare landscape with diminishing public research funding, increasing demand from institutions for clinical productivity, and decreased value of surgical education. To help the junior academic plastic surgeon, this article discusses the fundamental aspects of developing an early academic plastic surgery practice, rooted in clinical care, research, and education. Methods: Using published literature, expert opinion, and faculty interviews, the authors prepared this primer for education and guidance of plastic surgery residents considering a career in academic plastic surgery and early career academic plastic surgeons. Results: This primer highlights elements important to succeeding as a junior academic plastic surgeon including defining goals and priorities, institutional and financial support, mentorship, education of students and residents, developing a practice niche, promotion and tenure, and social support and burnout. Conclusion: The early career academic plastic surgeon can create an environment for academic success with appropriate institutional support, mentorship, personal, and social support, to progress toward promotion while minimizing burnout and professional exhaustion.